Robotic surgery for colorectal cancer in the Octogenarians. Issue 4 (21st May 2021) - Westrich, Gal; Mykoniatis, Ioannis; Stefan, Samuel; Siddiqi, Najaf; Ahmed, Yousra; Cross, Matthew; Nissan, Aviram; Khan, Jim S
Abstract: Background: We evaluated the short‐term outcomes of robotic colorectal cancer surgery in octogenarian patients, focussing on postoperative morbidity and survival. Methods: All patients ≥80 years in a prospective colorectal cancer database undergoing robotic curative colorectal cancer resection were included. Patient demographics, intraoperative findings, postoperative and oncological outcomes were recorded. Patients were further subdivided into two groups named: old (OG 80–85 years) and very old (VOG ≥ 86 years). Results: Fifty‐eight consecutive patients were included (median age, 83 years; male, 53.4%; median BMI, 26.5). Median total operative time was 230 min, median blood loss 20 ml, median length of stay 7 days. Major complications were seen in 12% of patients; and the 90‐day mortality rate was 1.7%. Complete R0 resection achieved in 93% of cases, average lymph node harvest was 22. Overall and disease‐free survival was 81% and 87.3%, respectively (median follow‐up 24.5 months). We noticed a trend towards more advanced lesion staging in the VOG, but only N2 stage was significant ( p  = 0.03). There was a statistically significant difference in overall survival in favour of the OG ( p  = 0.024). Conclusions: Robotic surgery is feasible in octogenarian patients undergoing curative colorectal cancer resection and is associated with good post‐operative outcomes and overall survival.